PERSEPSI GURU SD TERHADAP PENELITIAN TINDAKAN KELAS - Pramswari, Lungguh Puri (Mimbar Sekolah Dasar, 2016)
This study was set out of curiosity to know what kind of perception of elementary school teachers, in understanding and implementing classroom action research (CAR) to solve pedagogical-didactical problems that faced during the learning process. By survey method, this study is conducted to 63 the primary school teachers from first-grade class up to sixth grade one, derived from the three districts/city in West Java Province. In general, it can be described that all teachers stated how important CAR is, but most feel still constrained in implementing it.Keywords: perception, classroom action research, CAR.